Analisis Kunjungan Wisatawan Mancanegara melalui Pintu Udara, Laut dan Darat - Muhammad Ammar Alkautsar; Sekar Anisa Sely; Della Najunda K.S; Rofi Ilmi Fadhillah; Alfredo Edward Lazuardi; Triyana Muliawati (Indonesian Journal of Applied Mathematics, 2022)
In early 2020 the COVID-19 outbreak had entered the territory of Indonesia so a lockdown system began to be implemented in several areas to overcome the spread of the Covid-19 outbreak, including on the tourist arrivals route through land gates, air gates, and sea gates. This makes the writer interested in seeing the number of foreign tourists entering Indonesia through land, sea, and air gates in the hope of helping the government in increasing the number of foreign tourists visiting Indonesia by optimizing the facilities and infrastructure on the tourist arrivals route. In this study, the authors looked at the effect on the entrance data of foreign tourists and the trends or changes that existed in the data held. The research was conducted by applying the Kruskal-Wallis test to see the relationship between the entry pathways and the Cox-Stuart test to see changes in the data. These two tests are used because they are following the objectives and existing research data. After the tests were carried out, the results showed that there was a difference between the entry routes, and it was seen that the data had decreased, one of the contributing factors was the PSBB (Large-Scale Social Restrictions) due to the Covid-19 pandemic.